The Effect of Contextual Learning Model (CTL) on Students’ Learning Effectiveness in PKn Subjects in Elementary Schools - Dzakiyyah (International Journal of Students Education, 2025)
This study aims to identify the influence of the contextual learning model (CTL) on the effectiveness of student learning in the subject of Civics in elementary schools. The data collection for this study used the literature study method (library research) whose literature review aims to strengthen the analysis of various sources used. The data collection for this study was carried out by tracing articles found in reputable online journals using Google Scholar and documentation in the library. The results of this study indicate that the contextual learning model (CTL) greatly influences the increase in the effectiveness of student learning in the subject of Civics. This is due to the contextual learning model (CTL) which links the subject matter with real situations experienced by students, making it easier for them to understand and apply the knowledge gained. The conclusion of the study is that the contextual learning model (CTL) can increase the effectiveness of elementary school students’ learning which is expected to make learning in the subject of Civics more effective, students can complete assignments well, students can understand the subject matter more easily, and it is hoped that in the future the contextual learning model (CTL) can be applied with technology-based media to maximize student learning outcomes.